RETRACTED: The Impact of Work Enviroment, Information Technology, and Work Autonomy on Telework Adjusment of National Institute of Public Administration Employees During A Pandemic - Disya Praditina; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This research aims to determine the impact of Work Environment, Information Technology, and Work Autonomy on Telework Adjustment of National Institute of Public Administration Employees During a Pandemic. The population of this research used the Slovin sampling technique in which the population were 120 people. This research uses primary data with data collection method through questionnaires distributed to 120 respondents. The analysis technique uses multiple linear regression and uses the Static Product and Service Solution (SPSS) program with the 26.0 version. Based on the results of the partial research, it was discovered that Work Environment has been a positive and significant impact on Telework Adjustment. Information Technology has a positive and significant impact on Telework Adjustment. Work Autonomy has a positive and significant impact on Telework Adjustment.